2022
DOI: 10.1007/s11356-021-17805-8
|View full text |Cite
|
Sign up to set email alerts
|

Issues in sustainable supply chain’s futuristic technologies: a bibliometric and research trend analysis

Abstract: This paper presents a systematic review and bibliometric analysis in sustainable supply chain’s futuristic technologies. The analysis involves 1596 articles published in the Scopus database from 1990 to 2020. The analysis examines the research outcomes by observing trends in journals, authorship, and keywords. The outcomes are visualized using VOSviewer to show the graphical network of co-authorship and the author’s keywords. The results show that this research area has been a growing trend since 2016 and by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 131 publications
0
13
0
Order By: Relevance
“…They were adequately designing and managing the sustainable flow of products and services from raw material to finished goods is considered significant in the circular economy (Waqas et al 2021 ; Khan et al 2020 ; Ali et al 2022 ). In recent years, literature review confirmed that plenty of research articles had been published by researchers on SSCM corresponding to the green technological innovations (Wangsa et al 2022 ). Some researchers included it but not restricted to establishing the green technological innovations indicators for SSCM (Hussain and Malik 2020 ), examined and explored sustainable supply chain barriers and drivers and practices (Govindan and Hasanagic 2018 ), classified and filed the barriers hierarchy index to SSCM in the Chinese and Pakistani manufacturing industry (Jin et al 2022 ; Waqas et al 2018 ) and enabler of sustainable supply chain operations in Pakistani manufacturing industry (Hussain et al 2021 ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…They were adequately designing and managing the sustainable flow of products and services from raw material to finished goods is considered significant in the circular economy (Waqas et al 2021 ; Khan et al 2020 ; Ali et al 2022 ). In recent years, literature review confirmed that plenty of research articles had been published by researchers on SSCM corresponding to the green technological innovations (Wangsa et al 2022 ). Some researchers included it but not restricted to establishing the green technological innovations indicators for SSCM (Hussain and Malik 2020 ), examined and explored sustainable supply chain barriers and drivers and practices (Govindan and Hasanagic 2018 ), classified and filed the barriers hierarchy index to SSCM in the Chinese and Pakistani manufacturing industry (Jin et al 2022 ; Waqas et al 2018 ) and enabler of sustainable supply chain operations in Pakistani manufacturing industry (Hussain et al 2021 ).…”
Section: Introductionmentioning
confidence: 82%
“…The research teams have found lesser investigated and introduced the new trends and developments in SSCM, such as from raw material sourcing to production (Gedik and Avinc 2020 ), raw material storage (Baars et al 2021 ), sustainable product delivery system (Soleimani et al 2018 ; Khan et al 2022c ), worked on sustainable supply chain networks (Abdi et al 2020 ) and green reverse logistics. Unfortunately, some are activities still blurred regarding green technological and IT innovation in the literature in the field of SSCM, such as ambiguity in perceiving sustainable ideology, shortage of experts, and trust deficit of manufacturing firms in the adoption of SSCM (Wangsa et al 2022 ; Seman et al 2012 ; Khan et al 2021a , 2021b ) that is challenging supply chain, procurement managers, and practitioners. Apparently, the roadmap of SSCM research trends linked with technological innovation perspective still has vacuums in the literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Our reviewed papers were extracted from two electronic databases: Scopus and Web of Science . For a comprehensive set of search results, we developed three groups of keywords for the search strings that were used as input to the databases: “Decarbonisation” (Meyer, 2020; de Sousa Jabbour et al , 2019), “Supply chain” (Gebhardt et al , 2021; Jia et al , 2018) and “Technology” (Frederico et al , 2019; Oztemel and Gursev, 2020; Wangsa et al , 2022), as we aimed to study the current academic research on the role of technology in low-carbon SCM. Each group was connected by “AND” to take the concurrent set, and each keyword was concatenated within each group by “OR” to take the intersection set.…”
Section: Methodsmentioning
confidence: 99%
“…However, they do not examine the role of decarbonisation technologies in SCM. Wangsa et al (2022) consider both types of technologies, while a conceptual model and managerial implications remain absent.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, bibliographic data from Scopus was exported for all publications included in the full-text assessment (198 publications). VOSviewer produced a co-occurrence analysis of author keywords applying the full counting method following previous research (Wangsa et al, 2022). Two occurrences were used as the threshold to exclude 'outliers'.…”
Section: Content and Bibliometric Network Analysismentioning
confidence: 99%